Disparities in heart and lung transplantation. Issue 5 (October 2021) - Tsuang, Wayne; Khedraki, Rola; Hsich, Eileen
Abstract : Purpose of review: Cardiothoracic transplantation is the definitive therapy for end-stage heart and lung disease. In service to this population, disparities in access and care must be simultaneously understood and addressed. Recent findings: There are sex, race, geographic, age, and underlying disease disparities in both heart and lung transplantation. Women have reduced waitlist survival but improved posttransplant survival when compared with men for both heart and lung transplantation. Black patients have worse outcome compared with other races postheart transplant. Geographic disparities impact the likelihood of receiving heart or lung transplant and the growing number of patients with advanced age seeking transplant complicates discussions on survival benefit. Finally, underlying disease has affected outcomes for both heart and lung transplant and now are incorporated into the allocation system. Summary: Though heart and lung transplantation have several existing disparities, it remains to be seen how advancements in medical technology, changes in donor organ allocation policies, and growing experience in patient selection will impact these concerns.